2017
DOI: 10.12982/cmujns.2017.0024
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Steroids from the Bark of Aglaia argentea (Meliaceae)

Abstract: The study aimed to find a potential anticancer agent by isolating and identifying the chemical structure of compounds from Aglaia argentea and testing their cytotoxic effects against P-388 murine leukimia cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…The NMR spectra of 2 very similar with 1, the main difference was that compound 2 the absence of hydroxyl group at [δ H 4.21 (1H, m, H-7), δ C 74.5] and the presence of the methylene signal at [δ H 2.56 (1H, m, H-7a), 2.72 (1H, m, H-7b), δ C 32.4], suggested that 2 is 7-dehydroxy derivative of 1. In comparison of 2 with literature data of a stigmast-5-en-3βol (β-sitosterol) (Chaturvedula and Prakash, 2012;Harneti et al, 2014;Farabi et al, 2017), showed good agreement, therefore compound 2 was identified as a stigmast-5-en-3β-ol (βsitosterol), which shown in this plant for the first time. Figure 2.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The NMR spectra of 2 very similar with 1, the main difference was that compound 2 the absence of hydroxyl group at [δ H 4.21 (1H, m, H-7), δ C 74.5] and the presence of the methylene signal at [δ H 2.56 (1H, m, H-7a), 2.72 (1H, m, H-7b), δ C 32.4], suggested that 2 is 7-dehydroxy derivative of 1. In comparison of 2 with literature data of a stigmast-5-en-3βol (β-sitosterol) (Chaturvedula and Prakash, 2012;Harneti et al, 2014;Farabi et al, 2017), showed good agreement, therefore compound 2 was identified as a stigmast-5-en-3β-ol (βsitosterol), which shown in this plant for the first time. Figure 2.…”
Section: Resultssupporting
confidence: 55%
“…Another hydroxyl group was located at C-7 based on the correlation of H-6 and H-8 to oxygenated carbon at C-7 (δ C 74.5). A comparison of the NMR data of 1 with the data for 7α-Hydroxy-β-sitosterol (Chaturvedula and Prakash, 2012;Farabi et al, 2017), revealed that the structure of the two compounds were very similar, consequently compound 1 was identified as a 7α-Hydroxy-β-sitosterol, which shown in this plant for the first time. Compound 2 was obtained as a white needlelike crystal.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Tirucallane terpenoids isolated from stems of Picrasma quassinoids exhibited Cytotoxicity against gastric cancer cell line (MKN-28) via apoptosis, by activating caspase-3 and -9. Steroids from the bark of Aglaia argentea (Meliaceae) found to be cytotoxic against P-388 murine leukemia cells (Farabi et al, 2017). Phenol-rich mangrove plant, Avicennia marina (leaf ethyl acetate) extract showed Cytotoxicity and induced apoptosis in human breast cancer (AU565 and BT483) and liver cancer cells (HepG2 and Huh7) (Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigation reported that compounds isolated from the genus Dysoxylum exhibit diverse biological activities, which includes antitumor (Cao et al, 2013), antimicrobial (Gopalakrishnan et al, 2015), antibacterial (Hu et al, 2014b, antiparasitic (Lakhsmi et al, 2007), post-coital contraceptive (Das et al, 2013), and cytotoxic (Han et al, 2015;Ragasa et al, 2014;Kurimoto et al, 2011;Zhang et al, 2010;Ismail et al, 2009;Farabi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%